Silence and Listening: methods for the attainment of knowledge in Formative Arabic literature (2/8-3/9 cts.) - Samba Campos, Estrella (Anaquel de Estudios Árabes, 2021)
This article examines the narrative manifestations of ṣamt (silence) and istimāʿ (listening) in Formative Arabic literature. Both notions are embedded in Late Antiquity, which showcases the complex relationship between the oral and the written. While in the early ʿAbbāsid period, «word» and «speech» (kalām, naqṭ) represent the main channel for understanding the uninterrupted (mutawātir) revelation of prophetic tradition (ḥadīṯ), ṣamt (silence) and istimāʿ (listening) are distinguished as prerequisites for speaking in exemplary, moral conduct. Exegetical collections (muṣannafs) and early educational prose (adab) highlight both terms as cognitive practices of learning (taʿallum), in a developing urban, cosmopolitan, male-dominated society. Drawing on contributions to the phenomenology of sound, and its primacy as a medium in an auditory culture, the paper concludes that the emergence of narratives on ṣamt and istimāʿ conveys (i) an aural educational process, based on «listening» and «listeners» and (ii) the transmission and reception of knowledge (ʿilm), as an experience of sound.
Keywords: Silence; listening; ṣamt, istimāʿ; Formative Arabic literature; ʿAbbāsid literature; knowledge; education; ʿilm, adab; Phenomenology of sound